2020
DOI: 10.1177/1098300720924350
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Positive Behavioral Interventions and Supports Implementation: School Leaders Discuss Their Processes and Practices

Abstract: The purpose of the study was to investigate the leadership practices that elementary school administrators and leadership teams utilize to promote effective, successful, and sustainable schoolwide positive behavioral interventions and supports (SWPBIS). The study focused on the practices, processes, and challenges that administrators and school leaders indicated led to the successful implementation of the SWPBIS framework. Twenty-four school leaders (six administrators; 18 leadership team members) from five el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…These early childhood teachers suggested that the school dismissed younger students’ social-emotional difficulties and struggled to take an early approach to identifying children with behavioral issues. This finding is in line with other research showing that it is difficult for many U.S. elementary schools to move from a reactive approach to the proactive approach inherent in a social-emotional MTSS (Scaletta & Tejero Hughes, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…These early childhood teachers suggested that the school dismissed younger students’ social-emotional difficulties and struggled to take an early approach to identifying children with behavioral issues. This finding is in line with other research showing that it is difficult for many U.S. elementary schools to move from a reactive approach to the proactive approach inherent in a social-emotional MTSS (Scaletta & Tejero Hughes, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…It means that inclusive and participatory leadership in schools is very important to increase student participation and education. This is in line with the opinion of Scaletta and Tejero Hughes (2021), who states that leaders who are able to discuss decisions and invite the school community to implement them tend to make schools more effective. Discussions and deliberations, such as those held by the Principal of SMP Muhammadiyah 5 Kandangan, are important steps in ensuring that all parties are involved in the decision-making process, thereby making the school more effective.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, for universal EBPs like SWPBIS, it is common for educators to receive implementation support such as intensive training and coaching (e.g., Scaletta & Tejero Hughes, 2021). However, educators may be ambivalent or resistant to implementing new EBPs after receiving these implementation supports, resulting in suboptimal implementation and student outcomes (Zhang et al, 2022).…”
Section: Theory-informed Implementation Strategies To Enhance Educato...mentioning
confidence: 99%